Call for collaboration in researching the best practices in teaching ethical entrepreneurship: the conflict of money and ethics - Emeric Solymossy (Journal of Global Entrepreneurship Research, 2015)
Entrepreneurs seek opportunity, are organizational innovators, and engines of economic development. Pursuit of economic self-interest may manifest "guile," or deceit. As academics, we are charged by businesses (and society) to instruct students in functional topics as well as in the rules and policies of business, whether from a legalistic or procedural basis. This paper lays a literature and logic foundation for the culturally-influenced ethical differences having a significant impact on entrepreneurs and larger businesses due to differing ethical foundations and perspectives. Global differences in ethical values and practices combined with globalized markets, supply chains, and the labor workforce aggravate the likelihood of ethical conflicts. An outline of Western business education orientation, means and methods is presented, and initiates a call to collaborate with inquiry and understanding. While some readers may object to this article not further defining the problem beyond the domain of "Best Practices," and for not including elements of research design (methodology, instruments, or sampling technique), this author has attempted to define the need without injecting a bias or ethnocentric perspective. Global entrepreneurship research will benefit from understanding world-wide best practices in teaching business ethics, and such research is only valid if performed through true international collaboration; the essence of the Journal of Global Entrepreneurship Research.
Keywords: 650; Ethics; Entrepreneur; Cross-cultural; International; Values